Podstawowe problemy funkcjonowania swobody przepływu usług i próba ich rozwiązania w dyrektywie o usługach na rynku wewnętrznym: [Basic difficulties concerning the functioning of the freedom to provide services and an attempt to solve them in the Directive on services in the internal market] (Studia Prawnicze / The Legal Studies, 2007)
Swoboda świadczenia usług, obok swobód przepływu towarów, pracowników, kapitału i płatności oraz przedsiębiorczości, jest podstawowym filarem tworzącym rynek wewnętrzny Wspólnoty Europejskiej. Jednocześnie jak żadna inna napotyka wciąż duże przeszkody w rozwoju. Obecnie to właśnie usługodawcy zdają się być grupą, której z największym trudem przychodzi korzystanie z dobrodziejstw gospodarczej integracji w ramach rynku wewnętrznego. Chodzi głównie nie o takie przypadki, gdy podmiot wspólnotowy podejmuje na terytorium innego państwa stałą działalność usługową, zakładając agencję, oddział lub filię czy też przenosząc tam swój ośrodek życiowy (swoboda przedsiębiorczości), ale o sytuacje, w których usługi w państwie przyjmującym świadczone są w sposób czasowy, jednorazowy, incydentalny. W taki sposób w słynnym orzeczeniu w sprawie Gebharcfi korzystanie ze swobody przepływu usług, w opozycji do swobody przedsiębiorczości, scharakteryzował Europejski Trybunał Sprawiedliwości.  On 12 th December 2006 the Council and the European Parliament adopted the long expected Directive on services in the intemal market (2006/123/EC). The main objective of the directive is to facilitate the free circulation of services by removing key barriers to the freedom of establishment for providers of services and to the free movement of services itself. This paper deals with several crucial issues conceming this new Community development. First, it briefly summarizes the present State of the freedom to provide services, taking into account both Community doctrine and the ECJ’s jurispradence and showing main problems connected with practical operation of this freedom. Then the main reasons of growing importance of the services’ sector, namely its economic importance and the broad scope of the freedom to provide services are identified and examined. It is later pointed out, that facing this increasing significance of the free movement of services, Community law does not guarantee enough protection for those who want to provide cross-border services. This leads to the conclusion that a community secondary legislation is highly necessary. From this perspective, the arrival of the new Community legislation is highly appreciated. Thorough analysis conducted in this paper leads to the conclusion that the new directive does not solve all the problems relating to the freedom to provide services. Much will depend on the way of its implementation and on the forthcoming jurisprudence of the ECJ.